EMOTIONAL STABILITY AS A NECESSARY INDICATOR OF THE PROFESSIONALISM OF A FUTURE TEACHER - N.V. Hordiyenko (Academy of Cognitive and Natural Sciences, 2010)
The article deals with the theoretical substantiation of role of emotional flimness as a necessary index of future teacher's professional experience. The essence of the term and peculiarities of its displaying in the context of professional activity of teacher as his stability factor are revealed.